2016
DOI: 10.1155/2016/1462563
|View full text |Cite
|
Sign up to set email alerts
|

Decreased S100A9 Expression Promoted Rat Airway Smooth Muscle Cell Proliferation by Stimulating ROS Generation and Inhibiting p38 MAPK

Abstract: Background. Asthma is a disease with a core abnormality in airway smooth muscle function, and the proliferation of airway smooth muscle cells (ASMCs) plays a pivotal role in asthma airway remodeling. Our previous study showed that S100A9 (S100 calcium-binding protein A9; 400 and 800 ng/mL) significantly inhibited rat ASMCs proliferation at 48 h, and 50–800 ng/mL S100A9 (50, 100, 200, 400, and 800 ng/mL) also induced a lasting effect by significantly inhibiting rat ASMCs proliferation at 72 h in a dose-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
2
7
0
Order By: Relevance
“…7m, n), consistent with the impact on S100A9 expression of reduced Ca 2+ flux through RyRs (Fig. 5i, j) and previous reports on S100A9 repression during proliferation of airway smooth muscles 57 . These observations, the distribution of chromatin marks and general tendency of NE-association to keep chromatin repressed 58,59 lends support to the view that NE invaginations may play a role in genome regulation and cycles of gene repression and activation.
Fig.
…”
Section: Resultssupporting
confidence: 91%
“…7m, n), consistent with the impact on S100A9 expression of reduced Ca 2+ flux through RyRs (Fig. 5i, j) and previous reports on S100A9 repression during proliferation of airway smooth muscles 57 . These observations, the distribution of chromatin marks and general tendency of NE-association to keep chromatin repressed 58,59 lends support to the view that NE invaginations may play a role in genome regulation and cycles of gene repression and activation.
Fig.
…”
Section: Resultssupporting
confidence: 91%
“…These observations are therefore consistent with the idea that invaginations act to regulate anti-proliferative genes, that is until the proliferative phenotype [ 219 ] is ready to be engaged. During proliferation we noted loss of S100A9 expression (but not MLH1 expression), namely the emerin and BAF regulated gene whose expression was attenuated by blocking calcium flux through RyRs with tetracaine, which is consistent with previous reports on S100A9 repression during proliferation of airway smooth muscles [ 220 ]. These observations, the distribution of chromatin marks and general tendency of NE-association to keep chromatin repressed [ 221 , 222 ] lends support to the view that NE invaginations may play a role in genome regulation and cycles of gene repression and activation.…”
Section: More Than This: Lost In Proliferationsupporting
confidence: 92%
“…[87][88][89] Several studies revealed that CP, especially S100A9, modulates proliferation of tumour, epithelial and smooth muscle cells, while CP concentrations may differ significantly. [90][91][92][93] CP-induced proliferation was shown to be mediated via RAGE ligation and NF-кB activation in tumour cells, linking inflammation with tumorigenesis. 91 S100A9 may also bind to TLR4 to promote MAPK signalling and monocytic cell differentiation.…”
Section: Extracellular Biological Functions Of Cpmentioning
confidence: 99%